A computational study of ² JHH(gem) indirect spin-spin coupling constants in simple hydrides of the second and third periods - Alkorta, Ibon (2008)
Several theoretical methods have been used to compute ²JHH in neutral, anionic and cationic HXH hydrides, X being the 14 nuclei from Li to CI (28molecules). Since the calculations also provide ¹JXH spin‐spin coupling constants (SSCC), these have also been analyzed. The best results were obtained using Second-order polarization propagator approximation (SOPPA)/sadJ. The geminal coupling constants appear to be dependent on the electronegativity of the X-atom